2012
DOI: 10.1155/2012/597306
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Asthma: New Low-Molecular-Weight Causal Agents, 2000–2010

Abstract: Background. More than 400 agents have been documented as causing occupational asthma (OA). The list of low-molecular-weight (LMW) agents that have been identified as potential causes of OA is constantly expanding, emphasizing the need to continually update our knowledge by reviewing the literature. Objective. The objective of this paper was to identify all new LMW agents causing occupational asthma reported during the period 2000–2010. Methods. A Medline search was performed using the keywords occupational ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…More than 350 agents have already been recognised to cause asthma3 4 and new agents are reported each year 5. Most occupational asthmagens are low or high molecular weight sensitisers, but irritant exposures are receiving increasing attention 6 7…”
Section: Introductionmentioning
confidence: 99%
“…More than 350 agents have already been recognised to cause asthma3 4 and new agents are reported each year 5. Most occupational asthmagens are low or high molecular weight sensitisers, but irritant exposures are receiving increasing attention 6 7…”
Section: Introductionmentioning
confidence: 99%
“…New agents are frequently reported in the literature, as shown by Pralong et al 8 in their recent review, 41 new LMW agents having been reported between 2000 and 2010.…”
mentioning
confidence: 94%
“…Ingredients of cleaning products are mostly low molecular weight molecules for which readily accessible diagnostic methods such as skin tests or laboratory tests are also not available and a specific provocation test is often the only way to confirm the aetiological hypothesis. Comprehensive case investigation is difficult (time‐consuming and sometimes laborious) and is not always performed, which explains why documented cases of cleaning product‐induced OR/OA are scarce: none of the 41 new low‐molecular‐weight causal agents of OA identified in Medline during the period 2000–2010 were reported for cleaning purposes (except for ortho‐phthalaldehyde and a peracetic acid‐hydrogen peroxide mixture employed in the very particular setting of endoscope disinfection) [Pralong et al, ].…”
Section: Introductionmentioning
confidence: 99%